Bibliometric Analysis of Youtube Platform Research Trends Using the Vosviewer Application - Julia Yakir; Osthoff Valentin; Tamara Rosario (Journal Emerging Technologies in Education, 2023)
Background. Youtube is said to be a media called alternative media. This is said because YouTube makes it easy for teachers or students to be able to carry out learning very well and can make students have increased learning activities and material can be easily understood quickly. Purpose. The aim of this studyto find out the effect of using YouTube as an online learning material so that the teaching and learning process continues to run well). Method. The method used in this study is a bibliometric analysis technique that includes RIS data components indexed by journals and by discussing research on YouTube as a learning medium.. Results. This shows that YouTube learning media is well used as a learning medium. Conclusion. What can be taken is that YouTube learning media has a positive influence on ease of access, student interest in learning, and improving learning outcomes. In addition, research conducted using the keyword "YouTube Learning Media" over a period of time demonstrates the existence of broad research clusters, interactions, and trends in the context of the YouTube platform. The limitation of this research is using bibliometric data which is limited to indexed journals related to YouTube as a learning medium. This could lead to bias in the data sample, so the findings may not cover all relevant research on YouTube use as an instructional medium. The research recommendation is to conduct qualitative research to deepen understanding of students' and teachers' experiences in using YouTube as a learning medium. This research can involve interviews, observations, or case studies to gain deeper insight into the benefits, challenges, and effects of using YouTube in a learning context